FAKTOR- FAKTOR YANG MEMPENGARUHI PEMANFAATAN PERSONAL COMPUTER ( Studi Empiris di Lingkungan Industri Terboyo Semarang ) - Caecilia Sri Haryanti Sri Haryanti (Serat Acitya, 2020)
Data processing has been grown rapidly, from the manual data processing into the computer- based data processing which is know as Personal Computing. This would make all the data processing more effective and efficient. However, not all individuals can obtain the advantages and accept the existence of computer since the factors that affecting the attitude of the user also determine the computer’s usefulness. The main objective of this study is to examine empirically factors influencing the employer attitude in using the computer for data processing. Primary data gathered from the firm’s employees that were familiar with the use of computer. Data were collected and distributed by contact person, to the 106 respondents in Industrial area of Terboyo. This study found the presence of support in some hypotheses which are social factot long-term consequences and facilitating condition and their effect on computer utilization. Nevertheless, affect, complexity and job fit do not affect computer’s utilization. Stimultaneously, independent variables affect the computer’s utilization of manager.